Social and economic factors, maternal behaviours in pregnancy and neonatal adiposity in the PANDORA cohort. (March 2020) - Longmore, Danielle K.; Barr, Elizabeth L.M.; Barzi, Federica; Lee, I-Lynn; Kirkwood, Marie; Connors, Christine; Boyle, Jacqueline; O'Dea, Kerin; Zimmet, Paul; Oats, Jeremy; Catalano, Patrick; McIntyre, H. David; et al.
Highlights: Aboriginal women experience more social disadvantage and diabetes in pregnancy than Europid women. Smoking in pregnancy associated with preserved skinfold adiposity and reduced lean body mass. Limiting intake of 'fast' foods in pregnancy will likely improve offspring adiposity. Skinfold measures may identify risk for early onset obesity. Socio-economic inequity likely to have important influence on neonatal adiposity. Abstract: Background: Australian Indigenous women experience high rates of social disadvantage and type 2 diabetes (T2D) in pregnancy, but it is not known how social factors and maternal behaviours impact neonatal adiposity in offspring of women with hyperglycaemia in pregnancy. Methods: Participants were Indigenous (n = 404) and Europid (n = 240) women with gestational diabetes mellitus (GDM) or T2D in pregnancy and their offspring in the Pregnancy and Neonatal Diabetes Outcomes in Remote Australia (PANDORA) study. Social, economic factors, and maternal behaviours were measured in pregnancy and six neonatal anthropometric outcomes were examined after birth. Results: On univariate analysis, maternal education < 12 years (p = 0.03), unemployment (p = 0.001), welfare income vs no welfare income (p = 0.001), lower area based socio-economic score (p < 0.001), and fast food intake > 2 times/week (p = 0.002) were associated with increased sum of skinfolds (SSF) in offspring. Smoking was significantly associated with a reduction in anthropometric measures, except SSF. In multivariable models adjusted for ethnicity, BMI and hyperglycaemia, social and economic factors were no longer significant predictors of neonatal outcomes. Smoking was independently associated with a reduction in length, head circumference and fat free mass. Frequent fast food intake remained independently associated with SSF (β-coefficient 1.08 mm, p = 0.02). Conclusion: In women with hyperglycaemia in pregnancy, social factors were associated with neonatal adiposity, particularly skinfold measures. Promoting smoking cessation and limited intake of energy-dense, nutrient-poor foods in pregnancy are important to improve neonatal adiposity and lean mass outcomes. Addressing inequities in social and economic factors are likely to be important, particularly for Indigenous women or women experiencing social disadvantage.